Analysis and optimization of spherical shells with strain energy and stress leveling index as objectives - Mohan Rao, B.D.V. Chandra; Rao, N.V. Ramana (Journal of Structural Engineering, 2025)
This paper deals with the analysis and structural shape optimization of spherical shells. The finite element analysis of a spherical shell was carried out and then optimized using ANSYS. The objective of this paper is the shape optimization of a spherical shell with the prescribed movement directions of shape design variables. The total strain energy and stress leveling index of the structure were minimized with a constraint that the total volume of the structure remains constant. The shape of a spherical shell subjected to a u.d.l. is optimized and the results are validated by comparing it with a benchmark problem. The structural optimization variables used in ANSYS are the Design variables (Shape variables), State variables (Total volume), and the Objective function (Total strain energy/Stress leveling index). The sub- problem approximation method is used to optimize the spherical shell. The effect of prescribing the movement directions of the shape design variables (Horizontal, Vertical, Both horizontal and vertical directions) is investigated for the optimum shape of the structure. The global optimum shape is obtained when the shape design variables move in both the horizontal and vertical directions simultaneously. The total strain energy and stress leveling index of the structure were reduced by 90 pecent